A quantitative analysis of risk premia in the corporate bond market - Sara Cecchetti (Journal of Risk and Financial Management, 2020)
Measures of corporate credit risk incorporate compensation for unpredictable future changes in the credit environment and compensation for expected default losses. Since the launch of purchases of government securities and corporate securities by the European Central Bank, it has been discussed whether the observed reduction in corporate credit risk was due to the decrease in risk aversion favored by the monetary easing or by expectations of lower losses due to corporate defaults. This work introduces a new methodology to break down the factors that drive corporate credit risk, namely the premium linked to cyclical and monetary conditions and that linked to the restructuring of the companies. Untangling these two components makes it possible to quantify the drivers of excess returns in the corporate bond market.
Keywords: 330; bond excess return; credit default swap; distress risk premium; expected default frequency; jump-at-default risk premium